Role of Instagram in Promoting Extravagant Wedding Trends: An Analysis of Social Pressures on the Middle Class - Sumera Batool; Zaeem Yasin; Mehwish Islam (Journal of Management Practices, Humanities and Social Sciences, 2021)
Instagram is the most important platform for the advertisement of marriage events. People become more prone to sharing everything on their Instagram accounts, from personal to public. Wedding ceremonies are expanding in society, and every class tries to follow these patterns regardless of their economic condition. The study was conducted to find out the role of Instagram in promoting extravagant wedding trends among the middle-class young adults of Lahore it aimed to analyze the social pressures endured by middle-class parents due to the promotion of these trends. A triangulation methodology was opted to observe the consumption patterns of Instagram among the young adults through the survey method; in contrast, semi-structured interviews were conducted to analyze the kind of pressures faced by the parents of young adults. A sample of 300 respondents was selected through purposive sampling in the survey method. For Interviews, a sample of 6 parents was selected through the snowball sampling method. Hegemony and uses and Gratification theories as theoretical frameworks helped to develop narratives on the issues. The study concluded that Instagram consumption promotes extravagant wedding trends among young adults and increases social, financial and mental pressures on parents. This study is significant in the current scenario as the wedding ceremonies are expanding in every society, and every class tries to follow these patterns regardless of their economic condition. The study investigates the role of Instagram in promoting extravagant wedding trends and also discusses the pressures endured by the middle class.